A global bibliometric and systematic review of sustainable construction materials incorporating waste concrete powder - Eric Ababio Ohemeng; Molusiwa S. Ramabodu (Discover Sustainability)
Abstract In recent years, waste concrete powder (WCP) has emerged as a possible substitute for ordinary Portland cement (OPC), addressing concerns related to emissions of carbon dioxide (CO2) and solid waste handling. However, there is limited information on the trends in WCP related studies. This research attempts to investigate the current bibliometric state of WCP studies over the past 15 years. The Scopus database and the program VOSviewer were used for the retrieval of bibliometric data and graphic representation of networks. In total, 86 articles were used for the study. The Journal of Construction and Building Materials emerged as the leading source, with 27 publications and 451 citations. China ranks as the most productive country, contributing 63 publications and receiving 1372 citations. South Korea follows with 9 publications and 151 citations. It was revealed that WCP research has demonstrated steady growth, starting with just two publications in 2017 and increasing to 34 by 2024. Also, this study systematically reviewed important literature to explore various research areas related to WCP studies. It was found that WCP studies have been examined from approximately thirteen distinct perspectives. In conclusion, this study offers valuable insights into the evolution, focus areas, and global distribution of WCP research. For practitioners, the findings highlight emerging opportunities to incorporate WCP as a sustainable material in construction, supporting resource efficiency, cost reduction, and alignment with circular economy goals.